Implementasi Manajemen Mutu Di PTKIN dalam Menghadapi Tantangan dan Menawarkan Solusi Kebijakan - Desi Dwi Anissa; Agus Zaenul Fitri; As'aril Muhajir (Universitas Negeri Malang, 2025)
Abstract: State Islamic Religious Colleges (PTKIN) face major challenges in improving the quality of education amidst the dynamics of regulations, technological developments, and the demands of globalization. This study aims to analyze the implementation of quality management at PTKIN, identify the challenges faced, and formulate relevant and applicable policy solutions. The method used is a systematic literature review (SLR) by examining selected scientific articles and documents for the 2020– 2025 period that discuss quality management, challenges, and policies at PTKIN. The results of the study show that the implementation of quality management at PTKIN is influenced by internal factors such as limited human resources, infrastructure, and quality culture, as well as external factors in the form of policy changes and global competition. The discussion found that effective solutions that can be adopted include strengthening human resource training, optimizing the use of information technology, internalizing a quality culture, and strategic collaboration with various parties to support the sustainability of education quality. In conclusion, the success of the implementation of quality management at PTKIN is highly dependent on the synergy between strengthening internal policies, developing human resources, and adapting to external changes in order to improve the competitiveness and quality of graduates. Keywords: Quality Management, PTKIN, Challenges, Policy Solutions, Systematic Literature Review Abstrak: Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) menghadapi tantangan besar dalam meningkatkan mutu pendidikan di tengah dinamika regulasi, perkembangan teknologi, dan tuntutan globalisasi. Penelitian ini bertujuan untuk menganalisis implementasi manajemen mutu di PTKIN, mengidentifikasi tantangan yang dihadapi, serta merumuskan solusi kebijakan yang relevan dan aplikatif. Metode yang digunakan adalah systematic literature review (SLR) dengan menelaah artikel dan dokumen ilmiah terpilih periode 2020–2025 yang membahas manajemen mutu, tantangan, dan kebijakan di PTKIN. Hasil kajian menunjukkan bahwa implementasi manajemen mutu di PTKIN dipengaruhi oleh faktor internal seperti keterbatasan SDM, infrastruktur, dan budaya mutu, serta faktor eksternal berupa perubahan kebijakan dan persaingan global. Pembahasan menemukan bahwa solusi efektif yang dapat diadopsi meliputi penguatan pelatihan SDM, optimalisasi pemanfaatan teknologi informasi, internalisasi budaya mutu, serta kolaborasi strategis dengan berbagai pihak untuk mendukung keberlanjutan mutu pendidikan. Kesimpulannya, keberhasilan implementasi manajemen mutu di PTKIN sangat bergantung pada sinergi antara penguatan kebijakan internal, pengembangan SDM, dan adaptasi terhadap perubahan eksternal guna meningkatkan daya saing dan kualitas lulusan. Kata kunci: Manajemen Mutu, PTKIN, Tantangan, Solusi Kebijakan, Systematic Literature Review